The effects of various doses of gamma irradiation on spoilage and physico-chemical properties of mango (Mangifera indica var. carabao) puree - Ahmad, Maqbool 1935-
Two lots of mango puree, each with different initial microbial population, were irradiated with three doses of gamma rays of Co60. The control samples from each lot received no irradiation. Regular microbiological examinations were done on stored irradiated samples for thirty days. At the same time both objective and subjective tests (excluding flavor) were performed on the products. Results indicated that the logarithm of the number of surviving organisms was roughly an inverse linear function of the irradiation dose. A definite extension of storage life was observed with the highest level of irradiation dose (1,000-kilorad). Samples irradiated at the highest dose did not spoil even after the termination of the study period of thirty days. No direct effect of irradiation on pH, percent titrable acidity and percent soluble solids of mango puree was observed. However, during storage, a decreasing trend in the pH and percent soluble solids and an increasing trend in the percent titrable acidity of the irradiated samples were observed. Irradiation per se did not seem to affect the color of mango puree. However, during storage the irradiated samples showed color inferior to that of the fresh. Odor of the puree was adversely affected by irradiation and such effect was found persistent during storage.